Decreased Fecal Bacterial Diversity and Altered Microbiome in Children Colonized With Clostridium difficile. Issue 4 (April 2019) - Chen, Lea Ann; Hourigan, Suchitra K.; Grigoryan, Zoya; Gao, Zhan; Clemente, Jose C.; Rideout, Jai Ram; Chirumamilla, Sankar; Rabidazeh, Shervin; Saeed, Shehzad; Elson, Charles O.; Oliva-Hemker, Maria; Blaser, Martin J.; et al.
ABSTRACT: Objectives: The gut microbiome is believed to play a role in the susceptibility to and treatment of Clostridium difficile infections (CDIs). It is, however, unknown whether the gut microbiome is also affected by asymptomatic C difficile colonization. Our study aimed to evaluate the fecal microbiome of children based on C difficile colonization, and CDI risk factors, including antibiotic use and comorbid inflammatory bowel disease (IBD). Methods: Subjects with IBD and non-IBD controls were prospectively enrolled from pediatric clinics for a biobanking project (n = 113). A fecal sample was collected from each subject for research purposes only and was evaluated for asymptomatic toxigenic C difficile colonization. Fecal microbiome composition was determined by 16S rRNA sequencing. Results: We found reduced bacterial diversity and altered microbiome composition in subjects with C difficile colonization, concurrent antibiotic use, and/or concomitant IBD (all P  < 0.05). Accounting for antibiotic use and IBD status, children colonized with C difficile had significant enrichment in taxa from the genera Ruminococcus, Eggerthella, and Clostridium . Children without C difficile had increased relative abundances of Faecalibacterium and Rikenellaceae. Imputed metagenomic functions of those colonized were enriched for genes in oxidative phosphorylation and beta-lactam resistance, whereas in the subjects without C difficile, several functions in translation and metabolism were over-represented. Conclusions: In children, C difficile colonization, or factors that predispose to colonization such as antibiotic use and IBD status were associated with decreased gut bacterial diversity and altered microbiome composition. Averting such microbiome alterations may be a method to prevent or treat CDI. Abstract : Supplemental Digital Content is available in the text